Skin-specific transgenic overexpression of ovine β-catenin in mice - Wang, Jiankui; Cui, Kai; Hua, Guoying; Han, Deping; Yang, Zu; Li, Tun; Yang, Xue; Zhang, Yuanyuan; Cai, Ganxian; Deng, Xiaotian; Deng, Xuemei (Frontiers in Genetics, 2023)
β-catenin is a conserved molecule that plays an important role in hair follicle development. In this study, we generated skin-specific overexpression of ovine β-catenin in transgenic mice by pronuclear microinjection. Results of polymerase chain reaction (PCR) testing and Southern blot showed that the ovine β-catenin gene was successfully transferred into mice, and the exogenous β-catenin gene was passed down from the first to sixth generations. Furthermore, real-time fluorescent quantitative PCR (qRT-PCR) and western blot analysis showed that β-catenin mRNA was specifically expressed in the skin of transgenic mice. The analysis of F6 phenotypes showed that overexpression of β-catenin could increase hair follicle density by prematurely promoting the catagen-to-anagen transition. The results showed that ovine β-catenin could also promote hair follicle development in mice. We, therefore, demonstrate domestication traits in animals.